2020
DOI: 10.7150/jca.37267
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DUSP6 enhances chemotherapy-resistance of ovarian epithelial cancer by regulating the ERK signaling pathway

et al.

Abstract: Objective: DUSP6 is a negative regulator of the ERK signaling pathway and plays an important role in chemotherapy-resistance. Previously we showed that DUSP6 is overexpressed in ovarian cancer side population (SP) cells that possess cancer stem cell-like properties and are quiescent and chemotherapy-resistant. Here, we explore the effects of DUSP6 on chemotherapy-resistance by examining its regulation of the ERK signaling pathway and G0/G1 cell cycle arrest. Methods: mRNA and protein expression of DUSP6 and G0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The mRNA expression levels of DUSP6/8/10 were markedly up-regulated after LIN28A knockdown. As a member of the DUSP family, DUSP6/8/10 inhibits ERK activity to regulate MAPK signaling in ovarian epithelial cancer ( Gao et al, 2020 ), pancreatic cancer ( Liu et al, 2021 ), and human epidermal stem cells ( Hiratsuka et al, 2020 ). The increase in DUSP6/8/10 expression indicates inactivation of MAPK signaling ( Cornacchia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression levels of DUSP6/8/10 were markedly up-regulated after LIN28A knockdown. As a member of the DUSP family, DUSP6/8/10 inhibits ERK activity to regulate MAPK signaling in ovarian epithelial cancer ( Gao et al, 2020 ), pancreatic cancer ( Liu et al, 2021 ), and human epidermal stem cells ( Hiratsuka et al, 2020 ). The increase in DUSP6/8/10 expression indicates inactivation of MAPK signaling ( Cornacchia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…23 Several reports have revealed that DUSP6 is closely associated with chemotherapy resistance in a variety of cancers. [24][25][26] Because WTAP is the core catalytic component in the RNA m6A methyltransferase complex, we considered that m6A methylation contribute to dysregulation of DUSP6. Herein, we observed that DUSP6 was depleted by WTAP elimination and modified by WTAP-mediated m6A methylation as detected by MeRIP-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that DUSP6 is involved in various physiological and pathological processes in diverse malignancies 23 . Several reports have revealed that DUSP6 is closely associated with chemotherapy resistance in a variety of cancers 24–26 . Because WTAP is the core catalytic component in the RNA m6A methyltransferase complex, we considered that m6A methylation contribute to dysregulation of DUSP6.…”
Section: Discussionmentioning
confidence: 99%
“…Given that treatment with Huaier extract downregulated the expression of cyclinD3 (Fig. 2B), which is one of the downstream factors of ERK [17], we attempted to determine the changes of MEK/ERK related protein expression after Huaier extract treatment in NB cells. By treating the 3 NB cell lines with different concentrations of Huaier extract, the phosphorylation of MEK and ERK was significantly inhibited in dose-dependent manner (Fig.…”
Section: Huaier Extract Suppressed Mek/erk Signaling In Neuroblastomamentioning
confidence: 99%